Design and Analysis of The IFA Bandwidth Enhancement for 639 MHz UHF Channel - Rohadi, Erfan; Amalia, Amalia; Siradjuddin, Indrazno; Setiawan, Awan; Ronilaya, Ferdian; Andrie Asmara, Rosa; Saleh, Chairul; Firdaus Ali, Mochammad; Adzikirani, Adzikirani (International Journal of Engineering and Technology, 2018)
Bandwidth characteristic enhancement of the antenna is engaging and challenging problems for antenna engineers. The design of the 639 MHz frequency of the low-profile inverted F antenna (IFA) on a finite conducting plane proposed and its characteristics are analyzed numerically. The IFA is typically a narrowband antenna, due to the bandwidth enhancement the antenna parameters are considered. When the size of the conducting plane is 115 mm by 230 mm, the return loss bandwidth (-10 dB) becomes 2.4 % and the gain becomes 6.58 dB. The results found that when the height of the antenna reduced the return loss bandwidth becomes narrower. However, the return loss bandwidth can be improved by extending the length of the short stub. The gains of IFA are more than 6.5 dB in all the calculation conditions.Â  This means that the gain characteristics are not significantly affected by variations in short stub length, the antenna heights and the size of conducting plane. The results show that by extending the height of the antenna and enlarge the size of the conducting plane improved the bandwidth enhancement of the IFA. The proposed inverted F antenna is promising for the UHF channel receiver.Â Â